Chronic bilateral dacryoadenitis caused by SARS-CoV-2 infection: a case report - Bassem Awada (Journal of Medical Case Reports, 2023)
Abstract Background Dacryoadenitis is inflammation of the lacrimal gland, mainly caused by viral infection. It can also be caused by bacterial pathogens and non-infectious processes such as auto-immune diseases and malignancy. Chronic dacryoadenitis is rarely linked to SARS-CoV-2 infection, with only five reports in the literature. Report A 26-year-old Arab woman experienced chronic inflammatory dacryoadenitis after a mild SARS-CoV-2 infection, which was successfully treated with oral prednisone. Conclusions Dacryoadenitis can occur due to inflammation caused by either SARS-CoV-2 exposure. The treatment typically involves the administration of steroids, with duration to be decided based on clinical response.